Carers' experiences and perspectives of the use of anticholinergic medications in people living with dementia: Analysis of an online discussion forum - Bara'a Shawaqfeh; Carmel M. Hughes; Bernadette McGuinness; Heather E. Barry (Health Expectations)
Abstract Introduction There is concern about the use of anticholinergic medications in people living with dementia (PLWD). Such medicines may increase cognitive decline and may be associated with higher mortality in PLWD who take these medicines. The aim of this study was to analyse data from an online dementia discussion forum to explore the experiences and perspectives of PLWD and carers about the use of anticholinergic medicines in this population. Methods Following receipt of ethical approval, archived discussions (posts) from Dementia Talking Point, a fully public online forum for anyone affected by dementia, created and maintained by the Alzheimer's Society, were searched from the date of inception to January 2022 using a range of search terms including commonly used anticholinergic medicines. Posts, including any of the search terms, were assessed for relevance and analysed using inductive thematic analysis. Results Five hundred and fifty unique posts were analysed, all of which had been provided by carers, with no posts attributed to PLWD. The themes that encompassed carers' experiences were (1) motivators of prescribing, (2) perspectives on the process of prescribing and (3) the outcomes of prescribing. The dominant motivator of prescribing was the management of noncognitive symptoms, pre‐ and postdiagnosis of dementia. Carers' perspectives on the process of prescribing were informed by an assessment of the risk‐benefit of starting a medication and shared decision‐making between the carer and healthcare professional to a greater or lesser degree. The outcomes of prescribing were observing the effects of the medicines, which in turn influenced whether prescribing was reviewed and continued unchanged, continued but amended, reinitiated if the medicine had been previously stopped or discontinued (the process of deprescribing). Conclusion This study has provided unique insights into carers' experiences and perspectives about the use of anticholinergic medications in PLWD, highlighting how commonly these medications are prescribed for PLWD and carers' concerns about their use. There is a clear need for carers and PLWD to receive information about these medicines and healthcare professionals to consider how to optimise the use of these medicines to avoid adverse effects. Patient or Public Contribution This work was informed by findings from previous research studies focusing on optimising medicine use for people with dementia in primary care, in which interviews were conducted with PLWD, their carers and primary healthcare professionals. Although not strictly patient and public involvement, we utilised the feedback provided by key stakeholders to inform the research questions and aim/objectives of this study.